Advances in the management and translocation methodology of the endangered mollusk Patella ferruginea in artificial habitats of port infrastructures: implications for its conservation - García-Gómez, José Carlos; Cid-Iturbe, Amparo; Ostalé-Valriberas, Enrique; Espada, Rocío; Carballo, José Luis; Fa, Darren Andrew; García-Olaya, Carlos; Blanca-Sújar, Rocio (Frontiers in Marine Science, 2023)
The limpet (Patella ferruginea), endemic to the western Mediterranean, is the most endangered intertidal mollusk listed in the Habitats Directive (EU). The translocation methodology of this species is a scientific challenge faced by those port infrastructures – where there are established breeding subpopulations - that may be subject to emergency works, restoration, or extension of breakwaters. This study presents the results of an innovative two-phase pilot project (P1A/B and P2), involving the legally authorized translocation of individuals of this species obtained in three relocation experiments in the Marina of Puerto José Banús (Málaga) in July 2021 (phase 1: P1A and B) and May 2022 (phase 2: P2) (study period: July 2021-October 2022). The specimens translocated in both phases were from the same port except for those of P1B, which came from the Marbella Marina as an exceptional case. These translocations were undertaken on concrete breakwater tetrapod units. We show that the somewhat forced, slow and unregulated extraction of specimens to be translocated during the first experiment of the P1A pilot project was the main cause of mortality, as it generated an important exhaustion of the fixation musculature, which resulted in a low survival (66%) after the first month of transfer, whereas during the same period of time. In the subsequent experiments (where the problem was methodologically corrected, a fast extraction technique -less than 5 seconds-, regulated and without injuries), in P1B was 100%, in P2 with cage was 93.3%, and, in P2 without cage it was 83.3%, which reflected an improvement in translocation methodology. The results of this research are compared according to the descriptors of success and failure of each protocol in order to observe the differences and thus enable their replicability.